Withaferin A inhibits Epithelial to Mesenchymal Transition in Non-Small Cell Lung Cancer Cells. Issue 1 (December 2018) - Kyakulaga, Al; Aqil, Farrukh; Munagala, Radha; Gupta, Ramesh
Abstract Lung cancer is the leading cause of cancer-related deaths worldwide and in the United States. Despite recent advancements in treatment approaches, metastasis remains a major therapeutic challenge in lung cancer and explains the extremely poor prognosis. Epithelial to mesenchymal transition (EMT), a complex process of cellular reprogramming has become an attractive drug target because it plays a crucial role in the metastasis of non-small cell lung cancer (NSCLC). In the present study, we examined the effects of withaferin A (WFA), a plant-derived steroidal lactone on EMT in human NSCLC cell lines. First, we demonstrated that WFA displayed time- and concentration-dependent cytotoxicity on A549 and H1299 NSCLC cells. Then, cells were exposed to ≤ 0.5 µM WFA for ≤ 4 h to minimize cytotoxicity and determined its effects on EMT, cell adhesion, motility, migration, and invasion. EMT induction was performed by culturing cells in serum-free media containing TGFβ1 (5 ng/mL) and TNFα (25 ng/mL) for 48 h. We observed that pretreatment of cells with WFA inhibited cell adhesion, migration, and invasion of A549 and H1299 cells. Using western blot, immunofluorescence, and qRT-PCR analysis, we demonstrated that WFA suppressed TGFβ1 and TNFα-induced EMT in both cell lines. Mechanistically, WFA suppressed the phosphorylation and nuclear translocation of Smad2/3 and NF-κB in A549 and H1299 cells. Together, our study provides additional evidence demonstrating the inhibitory effects of WFA on EMT induction in NSCLC cells and further demonstrates the therapeutic potential of WFA against the metastasis in NSCLC.